(untitled) (Neo Scientific Peer Reviewed Journal, 2023)
In this article, the methodological aspects of the reforms implemented in the years of independence in Uzbekistan regarding the improvement of human spirituality are partially touched upon, and the role of personality development and youth education is discussed.